PRELIMINARY PHYTOCHEMICAL, PHYSICOCHEMICAL, ANTIOXIDANT AND ANTIMICROBIAL STUDIES OF CLEMATIS MONTANA LEAVES - Bhatt, Hemlata; Saklani, Sarla; Upadhayay, Kumud (International Journal of Current Pharmaceutical Research, 2016)
Objective: To evaluate the phytochemical, physicochemical, antimicrobial and in-vitro antioxidant activity of Clamentis montana (Family: Rananculaceae). Methods: The extracts were evaluated for antibacterial activity against S. aureus, B. subtilis, E. coli, P. aeruginosa by cup plate method. In-vitro antioxidant activity was done by DPPH, ferrous chelating and reducing power assay method. The physicochemical parameter like a loss on drying, total ash value, foreign matter, etc. was evaluated by standard protocol. Results: The extract showed significant antibacterial activity against all test strains when compared with standard drugs amoxicillin. The extract showed significant antioxidant activity by DPPH method, reducing power assay and ferrous chelating method. Conclusion: The extract showed a dose-dependent significant antibacterial and antioxidant activity.